Molecular Docking Study of Enzyme-Substrate Interaction in the Synthesis of Anandamide Synergists - Garcia Liñares, Guadalupe Eugenia (2017)
We have previously reported the synthesis of a series of twenty N-fatty acylamines analogs of anandamide, fifteen of them novel, following an enzymatic approach, in very good yield and a chemoselective way. The cytotoxic activity of all compounds and mixtures of anandamide and its analogues was evaluated in rat glioma C6 cells and these studies revealed that some of them greatly enhance the antitumor effect of anandamide, suggesting their possible application as an alternative treatment for cancer. Encouraged by these great results, hereby we present a thorough molecular modeling study of the interaction between seven representative different substrates and the lipase used in the synthesis with the aim of understanding the observed relation between structure and reactivity. Furthermore, this approach can be applied to better understand, and thus improve, innovative biocatalytic processes for the synthesis of new bioactive drugs or precursors.